Fragmentation and Monetary Policy in the Euro Area - Al-Eyd, Ali (IMF Working Papers; Working Paper ;, 2013)
The ECB has taken a range of actions to address bank funding problems, eliminate excessive risk in sovereign markets, and safeguard monetary transmission. But euro area financial markets have remained fragmented, driving retail interest rates in stressed markets far above those in the core. This has impeded the flow of credit and undermined the transmission of monetary policy. Analysis presented here indicates that the credit channel of monetary policy has broken down during the crisis, particularly in stressed markets, and that SMEs in these economies appear to be most affected by elevated lending rates.Given these stresses, the ECB can undertake additional targeted policy measures, including through additional term loans, collateral policies, and private asset purchases.